Hysteroscopic polypectomy decreases NF-?B1 expression in the mid-secretory endometrium of women with endometrial polyp - Bozkurt, Murat; Sahin, Levent; Ulas, Mustafa (Elsevier Science Bv, 2015)
Objectives: Endometrial polyps have been identified as a possible factor for sub-fertility, their implication on endometrial NF-kappa B1 activity; the central regulator of the immune system gene expression involved in implantation has yet been little studied. We evaluated the NF-kappa B1 level and NF-kappa B p65 expression in the endometrium before and after hysteroscopic removal of the endometrial polyp during the mid-secretory phase. Study design: Infertile women with polyp (n = 15) were enrolled. Unexplained infertile patients with normal endometrium (n = 5) and healthy fertile women (n = 5) were recruited as controls. Endometrial samples were obtained before and 4 months after the hysteroscopic polypectomy. NF-kappa B1 levels were analyzed by ELISA in the endometrium of all groups before and after polypectomy. The H-Score method was used to evaluate immunohistochemical NF-kappa B p65 expression in the endometrium. Results: NF-kappa B1 expression and NF-kappa B p65 immunoreactivity in the endornetrium were significantly higher in women with polyp compared to unexplained infertile and fertile controls. Hysteroscopic polypectomy resulted in a significant decrease in endometrium NF-kappa B1 and NF-kappa B p65 activity. Conclusions: Endometrium of women with endometrial polyp has abnormalities in expression of NF-kappa B1 and NF-kappa B p65 which may contribute to endometrial receptivity and so polyp related sub-fertility. Hysteroscopic polypectomy may help to the normalization of endometrial NF-kappa B concentrations. (C) 2015 Elsevier Ireland Ltd. All rights reserved.
Keywords: NF-kappa B1; Endometrial polyps; Hysteroscopic polypectomy